A SURVEY ON ATTACKS AND APPROACHES OF INTRUSION DETECTION SYSTEMS (International Journal of Advanced Research in Computer Science, 2017)
Now a day’s information of an organization floating over the internet that increases the traffic on the network, heavily uses of the internet give rise in traffic on the network as well as made the network data vulnerable. All this happened because of easy to access the data on the internet. So we needed a security mechanism to protect the sensitive data over the network. For protecting that information Intrusion Detection System (IDS) is placed in the system. IDS is a software or hardware device that deals with attacks by collecting information from a variety of system and network sources, then analyzing the symptoms of security problems. Network Intrusion Detection (NID) is an Intrusion Detection mechanism that attempts to discover unauthorized access to a computer network by analyzing traffic on the network. Host based Intrusion Detection (HID) analyses the user activities and decides that the user is authorized or not. There are lots of ways to implement an IDS system, and it depends on the usage of the systems or the requirements of an organization. This paper describes some or all of the main techniques to implement IDS. This paper aims towards the proper survey of intrusion detection system, the attacks and techniques to implement IDS, so that researchers can make use of it and can find the new techniques or ways to efficient implementation of IDS.